A residual strength model for the fatigue strengthening behavior of 2D needled CMCs. (November 2015) - Fang, Guangwu; Gao, Xiguang; Zhang, Sheng; Xue, Jiangang; Song, Yingdong; Wang, Fang
Highlights: A strengthening behavior of needled CMCs after fatigue was found. The residual strength firstly increases and then decreases as fatigue cycles increase. A model to describe this trend of residual strength was presented. Wear-in and wear-out mechanisms were developed to explain strengthening behavior. Abstract: An important result of our investigations of the fatigue response of Ceramic Matrix Composites (CMCs) is the modeling of the residual strength after fatigue loading. According to the experimental results, the residual tensile strength of 2D needled CMCs firstly increases and then decreases as the number of fatigue cycles increases. Based on the microstructure observations and the wear-in/wear-out mechanisms presented by previous researchers, a model is developed here to characterize the residual strength vs. the number of fatigue cycles for the composites. After parameter identification, the presented model describes the change of the residual strength quite well.